No difference in sexual behavior of adolescent girls following Human Papilloma Virus vaccination: a case study two districts in Uganda; Nakasongola and Luwero - Aujo, Judith Caroline; Bakeera-Kitaka, Sabrina; Kiguli, Sarah; Mirembe, Florence (BMC Public Health, 2014)
Vaccination against Human Papilloma Virus (HPV) before sexual debut has been recommended by WHO as a primary prevention strategy against cervical cancer. In Uganda, vaccination against HPV started as a demonstration project among young girls in Nakasongola; and Ibanda districts. Studies have suggested that vaccination against HPV could result in risky sexual behavior and increase the risk of early sexual debut. This study was done to compare the sexual behavior of HPV vaccinated and non vaccinated adolescent girls in two neighboring districts in Uganda; and to assess whether HPV vaccination had any influence on sexual behavior of vaccinated adolescent girls.
Keywords: Sexual behavior; Adolescent girls; Human Papilloma Virus vaccination; Uganda